PENGARUH PELATIHAN KEPEMIMPINAN TERHADAP PELAKSANAAN STANDAR MANAJEMEN PELAYANAN KEPERAWATAN KARU DALAM KOMITMEN PERAWAT DALAM MENGIMPLEMENTASIKAN MPKP - Yanti Sutriyanti; Derison Marsinova Bakaral; Surani Warsit (Politeknik Kesehatan Tanjung Karang, 2014)
Yanti Sutriyanti1,Derison Marsinova Bakara1, Surani Warsit11)1) Prodi Keperawatan Curup Poltekkes Kemenkes BengkuluEmail: derisonmarsinovab@yahoo.com Abstract: The effect Leadership Training on The implementation ofnursing careManagement standardsby the Head Nurse to Commitment Nursing to Implement MPKP. The application ofnursing carestandardsinthe roomis veryimportantfor the sustainability ofthe provision ofqualitynursing caretoclientswhereneeded for a leaderwhocanmove theheadnurseroomunderneathtowork according totheir role and functioninapplying themodel ofprofessional nursingpractice.Designresearch isquasyexperiment,form designused